Does land renting-in reduce grain production? Evidence from rural China. (January 2020) - Qiu, Tongwei; Boris Choy, S.T.; Li, Shangpu; He, Qinying; Luo, Biliang
Highlights: Most researchers argue that land renting-in leads to the cultivation of non-grain products in rural China, but they ignore that non-grain production increases farmers' labor cost, especially for migrants. So we re-assess the relationship between land renting-in and grain production. We find that land renting-in positively affects rice acreage, especially when there is less labor available for agriculture. We also find that the difference in mechanization between the production of grain crops and of cash crops means that the production of cash crops requires more labor; lessees facing labor constraints grow grain crops because labor costs are increasing rapidly in China. Abstract: China's grain security is an increasing global concern. Most researchers argue that land renting-in leads to the cultivation of non-grain products in rural China. We use household-level data collected in China to assess the relationship between land renting-in and grain production. Our results indicate that land renting-in positively affects rice acreage, especially when there is less labor available for agriculture. The channel of the effect is that lessees tend to increase the use of machinery in rice production, but not in the production of cash crops because the production of grain crops can be more easily mechanized in rural China. The Chinese government should still pay close attention to the cultivation of non-grain products caused by land renting-in because workers in the production of cash crops may also be easily replaced by new agricultural technologies.